IMPLEMENTASI PEMBIASAAN APEL PAGI DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA SEKOLAH DASAR - Yoga Wahyu Dwi Safitri; Sri Mulyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of morning assembly habituation in shaping students’ disciplinary character at SD Negeri Mulur 01, Bendosari District, Sukoharjo Regency, Academic Year 2025/2026. The research was motivated by the low level of student discipline, such as tardiness and lack of order during school activities. This study employed a qualitative descriptive approach with a case study design. Data were collected through observation and interviews with the principal, teachers, and students. The results showed that morning assembly was conducted routinely and systematically every day before learning activities, including lining up, flag respect, prayer, short surah memorization, singing national songs, and delivering information. This habituation effectively shaped students’ disciplinary character, as reflected in punctuality, rule compliance, and orderly participation. Supporting factors included teacher collaboration, adequate facilities, and a conducive school environment, while inhibiting factors included weather conditions and student tardiness. Overall, consistent and structured morning assembly habituation can be an effective strategy to develop students’ disciplinary character in elementary schools.